AI in Law: Urgency of the Implementation of Artificial Intelligence on Law Enforcement in Indonesia - Hary Abdul Hakim; Chrisna Bagus Edhita Praja; Sung Ming-Hsi (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: The advancement of Artificial Intelligence (AI) has marked the beginning of an age in digital technology, social economics, human needs, and professional conduct. A previous study shows a significant difference in the level of accuracy between Artificial Intelligence (AI) machines and human advocates in which AI machines turned out to be more accurate than advocates. However, the challenges are related to the inadequacy of laws in responding to the development of AI. Furthermore, Indonesian law enforcement officers lack awareness of the advantages of using AI to support their profession.Purpose/Objective Study: Hence, this study aims to analyze the urgency of implementing AI for law enforcement in providing legal services and the law enforcement process.Design/Methodology/Approach: The method used in this research is normative, empirical research with Statute and Conceptual Approach. Furthermore, the data uses primary and secondary data sources. Primary data was obtained through interviews with law enforcement officials. Meanwhile, secondary data sources are primary and secondary legal materials. Furthermore, it will be analyzed qualitatively and presented descriptively.Findings: Artificial Intelligence (AI) is crucial in assisting in developing services and law enforcement, especially for Indonesian law enforcement, which still relies on manual or conventional means to carry out its duties. Artificial Intelligence (AI) can bring benefits in terms of time efficiency and accuracy in assessing cases urgently needed by law enforcement. In terms of law enforcement's perception of the use of AI, they are placed as assistants who cannot entirely replace the law enforcement profession since Artificial Intelligence (AI) lacks human traits that law enforcement officers must possess.Paper Type: Research Article